Literacy Educators’ Perspectives on Transformation and Authenticity - Brenda Wright; Patricia Cranton; B. Allan Quigley (Adult Education Research Conference, 2007)
We discuss how adults with low literacy skills have transformed through education and also raise epistemological questions on education’s place in the transformation and learning process.